Activity scheduling for a robotic caretaker agent for the elderly. (27th December 2010) - Huang, Shell Ying; Zhang, Huiliang
A real-time robotic agent that takes care of an elderly person at home will need to schedule various tasks in real time. The deadlines of its tasks are generally soft (missing a deadline by a few minutes in most cases has no serious consequences). Another characteristic is that many tasks are preferably done close to some time points instead of as soon as possible. To support such time management behaviour, we propose to enrich the BDI agent framework with an extension which consists of two processing components, a priority changing function (PCF) selector and a priority controller. The priorities of desires/intentions are represented by their PCFs. A PCF is a function of both time and the utility value of a desire/intention. So it represents both the urgency and the importance (beneficial value) of a desire/intention. We propose a method of constructing PCFs which model the change of priorities of tasks as time passes. Simulation experiments show that sigmoid function can control the activities of an agent better than constant priorities with respect to getting tasks done with smaller mean earliness and smaller mean tardiness. A BDI agent built with this time management mechanism will try to complete its tasks at the right time. The order in which multiple goals and multiple intentions are handled will be flexible and time dependent.